ISLAMIC INSURANCE — TAKAFUL: PRINCIPLES AND OPPORTUNITIES - Shokhzod Khujamurotov; Ashraf Turdialiyev (TADQIQOTLAR, 2025)
Abstract: This article analyzes the essence, key principles, and distinguishing features of the Takaful system, a form of insurance compliant with Sharia law. The Takaful model is based on the principles of mutual assistance, risk-sharing, and fairness, and is characterized by its exclusion of elements prohibited in Islamic finance, such as interest (riba), gambling (maysir), and uncertainty (gharar). The article also examines the practical implementation of the Takaful system in countries like Malaysia and Saudi Arabia, and analyzes the opportunities and existing challenges of introducing it in Uzbekistan. In conclusion, Takaful is presented as a promising new direction in the insurance market, with suggestions for its gradual development in the country.